Renters vs. owners in the distribution of project benefits the Tondo code of policies - Reforma, Mila A. (Philippine Journal of Public Administration, 1981)
The Code of Policies for Tondo Foreshore defines the use and distribution of project benefits among the different types of families in Tondo. As a result of the enforcement of some of its provisions, it has reduced the incidence of ownership of more than one structure, absentee landlords, and illegal sale of structures, while increasing the number of those who have so far gained access to the direct benefits of the project. Analysis of the extent of multiple occupancy and of the characteristics of different types of families in the project area as well as other similar squatter settlements point to certain policy options that could ensure that similar future upgrading efforts are able to reach appropriate by more beneficiaries. Foremost of these include: (1) pilot testing of an innovative tenure arrangement; (2) the adoption of a code of policies similar to that of Tondo in other project sites including strict enforcement of its provisions; and (3) the inclusion of certain types of renter families as direct beneficiaries of the project.